FeS2 Nanoparticles Encapsulated in S/N Co-Doped Carbon Nanofibers With a Three-Dimensional Multi-Channel Structure for Lithium-Ion Batteries - Cao, Xiaochang; Zhang, Yi; Luo, Chujiang; Yin, Yansheng; Huang, Yingying (Frontiers in Chemistry, 2022)
Pyrite (FeS2) is one of the potential candidates for advanced rechargeable Li-ion batteries (LIBs) owing to its inherent capacity (849 mAh g-1), environmental friendliness and abundant natural resources. However, the volume expansion of FeS2 and the dissolution of polysulfide in the electrochemical reaction severely limit its application in the field of energy conversion and storage. Herein, FeS2 nanoparticles are encapsulated in S/N co-doped three-dimensional multi-channel structural carbon nanofibers (FeS2@CNFs) through the electrospinning method. As a cathode material for LIBs, FeS2@CNFs demonstrated excellent rate property and cyclic stability. The 3FeS2@CNFs (weight ratio of FeS2 is 30%) present the initial capacity of 1336.7 mAh g-1 and remain 856.5 mAh g-1 at 0.02 A g-1 after 100 circles. The favorable electrochemical properties confirmed that carbon nanofibers can enhance the electroconductivity of electrodes, reduce volume collapse of FeS2 and remit the dissolution of polysulfide during Li+ ions insertion/de-insertion process. In addition, S/N co-doped can supply abundant active sites for electrochemical reactions, providing enough space for Li+ ions storage. The results indicate that 3FeS2@CNFs is a cathode with a development prospect for LIBs.